Holy Cows and Constitutional Nationalism in Nepal. - MALAGODI, MARA (Asian Ethnology, 2021)
The way in which the Nepali state has framed over the centuries the legal framework protecting the cow--Hinduism's sacred animal--illuminates the intimate relationship between state-framed nation-building and the management of sociocultural diversity in Nepal, the only other Hindu-majority state in the world alongside India. Nepal's 2015 Constitution, while declaring the state secular, continues to grant Hinduism a privileged place and to define the cow as Nepal's national animal. To understand the symbolic significance of these constitutional provisions in the construction of the Nepali nation and their material impact on Nepal's marginalized groups, it is crucial to analyze their historical development and their relationship to other parts of the constitution and to ordinary laws criminalizing cow slaughter. This article argues that cow protection has come to signify a vision of state authority that privileges the symbols of the majority over the rights of the minority--a vision channeled through the coercive instrument of law.